2020
DOI: 10.1017/rdc.2020.20
|View full text |Cite
|
Sign up to set email alerts
|

Prescreening Hydraulic Lime-Binders for Disordered Calcite in Caesarea Maritima: Characterizing the Chemical Environment Using FTIR

Abstract: Hydraulic lime binders are considered a technological marvel which revolutionized construction techniques in antiquity. The core material is made of a binder that is a mixture of calcite and hydraulic phases, which are amorphous silicate compounds that nanostructurally polymerize into insoluble phases that harden even underwater, formed during the reaction between lime and reactive silicates such as volcanic ash. This is also what makes hydraulic lime so hard to radiocarbon (14C) date. These insoluble phases c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 41 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…In most findings on building materials reported in archaeological sources, identification is visual because the shells can still be seen, although partially crushed [37]. Regarding scientific articles on the analytical determination of shells in mortars, aragonite has been revealed by FTIR spectroscopy and XRD in Roman mortars from Caesarea Maritima [38] and in wall paintings exclusively from the Roman and Hellenistic eras [39][40][41][42][43][44]. Some of these authors have also suggested that aragonite may have been used as a pigment too, alone in white areas or mixed with other pigments, as described in treatises [6].…”
Section: Discussionmentioning
confidence: 99%
“…In most findings on building materials reported in archaeological sources, identification is visual because the shells can still be seen, although partially crushed [37]. Regarding scientific articles on the analytical determination of shells in mortars, aragonite has been revealed by FTIR spectroscopy and XRD in Roman mortars from Caesarea Maritima [38] and in wall paintings exclusively from the Roman and Hellenistic eras [39][40][41][42][43][44]. Some of these authors have also suggested that aragonite may have been used as a pigment too, alone in white areas or mixed with other pigments, as described in treatises [6].…”
Section: Discussionmentioning
confidence: 99%